Measurements of Explosion-Induced Shock Waves in Ice and Snow, Greenland, 1957 and 1958 - Ingram, L. F.; Halper, S. H. (1960)
Pressure-time histories of shock waves, both above and below the surface, were obtained in the proximity of high-explosive charges detonated in ice and snow. Measurements with piezoelectric gages were obtained from 15 explosions in glacial ice and 36 explosions in deep snow. Four different charge types, with weights ranging from 2.5 to 160 lb, were fired. Charge positions ranged from above the surface to a depth of 23.10 ft below the surface. The resulting pressure, impulse, and shock-velocity data exhibited considerable scatter when plotted as a function of reduced distance. At distances of 2 to 20 ft from the charge, the mean shock velocities were 11,500 fps in ice and 4200 fps in snow.